Anti-breast cancer effects of dairy protein active peptides, dairy products, and dairy protein-based nanoparticles - Zhang, Deju; Yuan, Ying; Xiong, Juan; Zeng, Qingdong; Gan, Yiming; Jiang, Kai; Xie, Ni (Frontiers in Pharmacology, 2024)
Breast cancer is the most frequently diagnosed and fatal cancer among women worldwide. Dairy protein-derived peptides and dairy products are important parts of the daily human diet and have shown promising activities in suppressing the proliferation, migration, and invasion of breast cancer cells, both in vitro and in vivo. Most of the review literature employs meta-analysis methods to explore the association between dairy intake and breast cancer risk. However, there is a lack of comprehensive summary regarding the anti-breast cancer properties of dairy protein-derived peptides, dairy products, and dairy protein-based nanoparticles as well as their underlying mechanisms of action. Therefore, the present study discussed the breast cancer inhibitory effects and mechanisms of active peptides derived from various dairy protein sources. Additionally, the characteristics, anti-breast cancer activities and active components of several types of dairy products, including fermented milk, yogurt and cheeses, were summarized. Furthermore, the preparation methods and therapeutic effects of various dairy protein-containing nanoparticle delivery systems for breast cancer therapy were briefly described. Lastly, this work also provided an overview of what is currently known about the anti-breast cancer effects of dairy products in clinical studies. Our review will be of interest to the development of natural anticancer drugs.